2005
DOI: 10.1183/09031936.05.00010805
|View full text |Cite
|
Sign up to set email alerts
|

dsRNA enhances eotaxin-3 production through interleukin-4 receptor upregulation in airway epithelial cells

Abstract: The exacerbation of asthma during viral infections is mainly explained by neutrophils infiltrating into the airways. However, enhanced functions of eosinophils are also observed. The aim of this study was to reveal the mechanism of how eosinophils are activated during and after viral infection of the airways, using a model of viral infection.A synthetic double-stranded RNA, poly inosinic-cytidyric acid (poly(IC)), was transfected to a human airway epithelial cell line (BEAS-2B) and the primary bronchial epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…TSLP-activated DC express OX40L and promote the differentiation of TNF-␣-producing inflammatory Th2 cells from naive T cells (24). In addition, TLR3 activation strongly induced eosinophil-recruiting chemokines in the presence of Th2 cytokines (51,52). Together, these findings suggest that viral infection in a Th2 environment may amplify allergic reactions locally.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…TSLP-activated DC express OX40L and promote the differentiation of TNF-␣-producing inflammatory Th2 cells from naive T cells (24). In addition, TLR3 activation strongly induced eosinophil-recruiting chemokines in the presence of Th2 cytokines (51,52). Together, these findings suggest that viral infection in a Th2 environment may amplify allergic reactions locally.…”
Section: Discussionmentioning
confidence: 52%
“…Enhancement of CCL26 by the combination of IL-4 and dsRNA was found to be a secondary effect of the induction of the IL-4 receptor by dsRNA in airway epithelial cells (52). In the present study of TSLP expression, dsRNA and IL-4 stimulated NHBE rapidly (Fig.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Previous studies have shown that poly(I:C) or virus-derived dsRNA increases the production of cytokines and chemokines, including IL-6, CCL5, CXCL8, and CXCL10 in primary cultures or immortalized bronchial epithelial cells, such as BEAS2B (15)(16)(17)(18)(19)(20). In the present study, we have confirmed that poly(I:C) is also a potent stimulant of the synthesis of CCL5 in BSMC, as well as of IL-6, CXCL8, and CXCL10.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that dsRNA, as a virus genome fragment or as a replicative intermediate of RNA virus (14), induces the production of chemokines, such as CCL5, MCP-1/CCL2, eotaxin-3/CCL26, IL-8/CXCL8, and IFN-inducible protein-10/ CXCL10 in respiratory epithelial cells (15)(16)(17)(18)(19)(20). TLR3, a receptor for dsRNA, is expressed in respiratory epithelial cells, as well as in dendritic cells, mast cells, and fibroblasts (21)(22)(23).…”
Section: Tlr3-mediated Synthesis and Release Of Eotaxin-1/ccl11 From mentioning
confidence: 99%